2001
DOI: 10.1111/j.1553-2712.2001.tb01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Evaluation of Chest Pain Using Exercise Stress Echocardiography

Abstract: Abstract. Objective: Patients with a low risk of coronary artery disease (CAD) presenting to the emergency department (ED) with chest pain pose a diagnostic dilemma because a small percentage will suffer an acute myocardial infarction (MI) and sudden death. The authors conducted this study to determine whether exercise stress echocardiography (ESE) could be used to further support the safe discharge of these low-risk patients. Methods: A convenience sample of patients Ն30 years of age without a prior cardiac h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
(22 reference statements)
2
10
0
Order By: Relevance
“…Results of the present study are consistent with a large, growing body of evidence suggesting the merits of stress testing for stratifying patients in chest pain unit [23][24][25][26][27][28]. In particular, a negative stress-imaging test has a very high negative predictive value in these patients.…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…Results of the present study are consistent with a large, growing body of evidence suggesting the merits of stress testing for stratifying patients in chest pain unit [23][24][25][26][27][28]. In particular, a negative stress-imaging test has a very high negative predictive value in these patients.…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…Patients who are at low risk for ACS because of negative initial cardiac biomarkers and normal or nondiagnostic ECG examinations, but in whom the source of chest pain is not readily identified, are a cohort whose management is notably inefficient [4][5][6][7]. The Funding for this study was provided through the Walker Fund of the Harvard Ph.D.…”
Section: A R D I a C I M Ag I Ng • O R Ig I N A L R E S E A Rc Hmentioning
confidence: 99%
“…American College of Cardiology (ACC) and the American Heart Association (AHA) recommend further evaluation for these patients, but their hospitalizations typically result in benign diagnoses [5,8,9]. Because ACS is rare in the absence of coronary atherosclerotic plaque, several researchers have suggested that the incorporation of noninvasive CT coronary angiography may improve the triage of patients with acute chest pain and reduce health care costs [3,[10][11][12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from 5 studies of echocardiography performed in adult ED patients presenting with chest pain, negative cardiac enzymes, and non-diagnostic ECG's demonstrated decreased mean length of stay and reduced costs and predicted a low cardiovascular event rate (LOE 1 260 ; LOE 4 [261][262][263][264] ).…”
Section: Consensus On Science Statementsmentioning
confidence: 99%